Supply chain drivers as a competitive advantage in hospitality company: A case study - Xue, Ting Lim; Lee, Khai Loon (Penerbit UMP, 2022)
Facilities, inventory, transportation, information, sourcing and pricing are the six supply chain drivers that determine the capability of gaining competitive advantage within a supply chain management. The constant growth of tourism industry in Malaysia has led to the rise of the hospitality industry over the recent years. However, some industries are still using inefficient and less responsive strategies to run their supply chain activities. Therefore, the supply chain drivers will be investigated based on their performance on achieving competitive advantage in hospitality company. The qualitative method used is by interviewing the manager of the selected hospitality company with interview protocol, which is a semistructured questionnaire. The qualitative data were analysed using qualitative data analysis software, ATLAS.ti. The result indicated that a good use of six supply chain drivers will definitely help a hospitality company in achieving the balance between responsiveness and efficiency. This study concluded that the performance of supply chain drivers is relatively important, to boost a hospitality company to gain their competitive advantage among competitors. Therefore, this study can be relevant for hospitality company to know how to gain competitive advantage through the supply chain driver.